1990
DOI: 10.1161/01.res.67.2.525
|View full text |Cite
|
Sign up to set email alerts
|

Isolated guinea pig coronary smooth muscle cells. Acetylcholine induces hyperpolarization due to sarcoplasmic reticulum calcium release activating potassium channels.

Abstract: Smooth muscle cells, dispersed from the circumflex coronary artery of the guinea pig, were studied with the whole-cell configuration of the patch-clamp. The resting potential of about -40 mV was superimposed by spikelike hyperpolarizations (SLHs) up to -20 mV amplitude. The SLHs resulted from spontaneous transient outward currents (spontaneous TOCs) measured under voltage-clamp (-40 or -50 mV). Acetylcholine (ACh; 10 microM) increased SLHs and TOCs in amplitude and frequency. Atropine blocked the ACh effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 12 publications
(4 reference statements)
1
30
0
Order By: Relevance
“…The Ca 2ϩ spark-activated transient BK current in GBSM caused a transient hyperpolarization up to 37 mV, similar to that described previously for arterial myocytes (18). Taking into account the high frequency of BK currents, even in resting conditions, spontaneous Ca 2ϩ sparks and the resultant hyperpolarizations could decrease GBSM excitability by decreasing the open-state probability of VOCCs.…”
Section: Discussionsupporting
confidence: 83%
“…The Ca 2ϩ spark-activated transient BK current in GBSM caused a transient hyperpolarization up to 37 mV, similar to that described previously for arterial myocytes (18). Taking into account the high frequency of BK currents, even in resting conditions, spontaneous Ca 2ϩ sparks and the resultant hyperpolarizations could decrease GBSM excitability by decreasing the open-state probability of VOCCs.…”
Section: Discussionsupporting
confidence: 83%
“…The fact that even the fast and small [Ca 2ϩ ] i increases associated with sparks control the plasmalemma voltage (10,24,27) provides a dynamic link between Ca 2ϩ stores and multiple plasma membrane Ca 2ϩ channels. If agonists lead to depletion of Ca 2ϩ stores, it is likely that the resultant focal activation of CCE and L-type Ca 2ϩ channels would replenish the stores and initiate muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that internal application of low molecular weight heparin (MW, approximately 6000) effectively inhibits the binding of inositol triphosphate (IP3) to the 'P3-receptor (Ganitkevich & Isenberg, 1990; Komori & Bolton, 1991;Takeda et al 1991). Figure 4 shows the effect of internal application of heparin on the response of Ia to NA.…”
Section: Methodsmentioning
confidence: 99%